Mapping the Condition of Seagrasses Beds in Ternate -Tidore Waters, and Surrounding Areas - Simon I. Patty (Jurnal Ilmiah PLATAX, 2016)
Seagrass beds is one of the most prolific shallow water ecosystems, having ecological function in the life of the various marine organisms and other coastal systems. Data and information of seagrass condition in the waters of Ternate, Tidore and surrounding areas are still hardly unexplored. This study aimed to describe the spatial distribution information of seagrass cover percentage, seagrass conditions and environmental characteristics. The basic data used for mapping of seagrass is Landsat 8 on a path 110 row 59 recordings in July 2015. Analysis of overlaying and the interpretation of the seagrass distribution software using "ERMapper, Image Analysis 1.1 on ArcGIS ArcView 3.2 and 10.1". Field test was conducted on frame 50 x 50 cm squares, each square of the recorded species of seagrasses and cover percentage value. Condition assessment based on seagrass cover by (Rahmawati et al., 2014) and (KMLH, 2004). The results show that there are eight species of seagrass found in the waters of the island of Ternate, Tidore and Hiri Maitara island. The highest percentage in the seagrass cover was found in Maitara islands and Hiri Island, i.e â‰¥ 50%. Seagrass cover conditions in general are relatively "moderate", but the health conditions are less healthy / less wealthy (30 to 59.9%). Keywords: Seagrass beds, seagrass conditions, mapping, satelite image ABSTRAK Padang lamun merupakan salah satu ekosistem perairan dangkal yang paling produktif, mempunyaiÂ  fungsi ekologis dalam kehidupan berbagai organisme laut dan sistem pesisir lainnya.Â  InformasiÂ  dataÂ  padangÂ  lamunÂ  diÂ  perairan Ternate, Tidore dan sekitarnya masih belum tereksplorasi dengan baik. Penelitian ini bertujuanÂ  mendeskripsikanÂ  informasiÂ  secaraÂ  spasialÂ  sebaranÂ  lamun,Â  persentaseÂ  tutupan, kondisi lamun dan karakteristik lingkungannya. Data dasar yang digunakan untuk pemetaan padang lamun adalah citra Landsat 8 pada path 110 row 59 rekaman JuliÂ  2015. Analisis tumpang susun dan interpretasi sebaran lamun dengan menngunakan perangkat lunak â€œErmapper, Image Analysis 1.1 pada ArcView 3.2 dan â€œArcGIS 10.1â€. Uji lapangan dilakukan pada frame kuadrat 50 x 50 cm, disetiap kuadrat dicatat jenis lamun dan nilai persentase tutupan.Â  Penilaian kondisi lamun berdasarkan tutupan menurut (Rahmawati dkk., 2014) dan (KMLH, 2004). Hasilnya menunjukkan bahwaÂ  terdapat 8 jenis lamun yang ditemukan di perairan pulau Ternate, pulau Tidore, pulau Hiri dan pulau Maitara. Presentase tutupan lamun tertinggi terdapat di pulau Maitara dan pulau Hiri yaitu â‰¥ 50 %. Kondisi lamun pada umumnya memiliki tutupan tergolong â€œsedangâ€, namun kondisinya kurang sehat/kurang kaya (30-59,9%). Kata kunci: Padang lamun, kondisi lamun, pemetaan, citra satelit Â  1 Proyek Penelitian RHM-COREMAP, 2015 2 UPT. Loka Konservasi Biota Laut Bitung-LIPI